Tīmekļa vietnes aizmugursistēmas ātrdarbības uzlabošana mērogojamības nodrošināšanai - Juraga, Arnis (Latvijas Universitāte, 2018)
Kvalifikācijas darbā “Tīmekļa vietnes aizmugursistēmas ātrdarbības uzlabošana mērogojamības nodrošināšanai” ir veikta tiešsaistes interneta veikala sistēmas, kas balstīta uz atklātā koda ietvara Opencart, izstrāde veiktspējas uzlabošanai. Uzlabojumi veikti sistēmas dzinēja PHP kodā un MySQL DBPS, panākot efektīvāku sistēmas resursu izmantošanu. Ieviests meklēšanas dzinējs Sphinxsearch un uzlabota satura kešdarbe. Sistēma nodrošina atbilstošu ātrdarbību pie 1 000 000 produktu vienībām un 14 000 produktu kategorijām. Tīmekļa vietne tiek pilnvērtīgi izmantota produkcijā.

In the qualification work - “Web site back-end response speed improvement for scalability support” was developed improvements for e-commerce system based on open-source “Opencart”. Improvements were made in the Opencart engine source code PHP side, together with improvements into MySQL database requests and structure. As a result was overall system performance and reduced system used resources. There was implemented search engine Sphinxsearch and improved the caching system. The system is planned to serve in required execution time limits and system load products catalog, with up to 1 000 000 products and 14 000 product categories. The system has been implemented and running in real life.
Web site back-end response speed improvement for scalability support
Keywords: Datorzinātne; PHP performance; MySQL performance; e-commerce; Sphinxsearch; MVC